A novel analytical hybrid optimization methodology for maximizing renewable energy integration in radial distribution networks - Fateh Ouali; Narimen Aouzellag Lahaçani; Yanis Hamoudi (International Journal of Applied Power Engineering (IJAPE), 2026)
Integrating distributed generation (DG) units into radial distribution systems (RDS) presents significant challenges, including voltage instability, power losses, and compliance with modern grid standards. To address these limitations, this study proposes a novel hybrid optimization methodology that combines advanced mathematical models with iterative power flow analysis. The approach introduces a multi-objective optimization framework that integrates voltage sensitivity factors, power loss indices, and voltage stability measures. A key innovation is the use of voltage stability indices (VSIs) as dynamic weighting factors to guide the optimization process, ensuring a balanced trade-off between minimizing power losses and enhancing network stability. This framework provides a precise and scalable solution for optimizing DG placement and sizing simultaneously. The methodology is validated on the IEEE 33-bus distribution system, demonstrating a 68% reduction in power losses, a 4.88% improvement in voltage stability, and a 70.4% DG integration rate, all achieved without altering the network configuration. These results highlight the proposed framework’s potential to enhance the resilience, efficiency, and reliability of RDS, offering a robust and standards-compliant solution for DG integration.